2007
DOI: 10.1037/cjep2007031
|View full text |Cite
|
Sign up to set email alerts
|

L'influence de la taille typique des objets dans une tâche de catégorisation.

Abstract: This study explores the influence of typical size during a categorization task. The specificity of this experimental work is based on the homogeneity of the graphic stimuli size. We have created a typical size standard of our stimuli, that concerns the real size of the objects represented by the drawings of homogeneous sizes. Then, a priming experiment was performed in which the prime and target drawings had two types of relations: a typical size, and a categorial. The participants are naïve as to the typical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Second, some studies suggested that the familiar size of objects can be automatically retrieved from memory. For instance, Ferrier, Staudt, Reilhac, Jiménez and Brouillet (2007) reported that objects associated with a large or small familiar size prime categorical judgments of objects with a close familiar size compared to objects with an important size difference. It is noteworthy that in this experiment, objects were presented with a constant visual size supporting the critical involvement of the familiar size rather than the visual one (see also Long, Konkle, Cohen & Alvarez, 2016;Long & Konkle, 2017 for converging evidences).…”
Section: Introductionmentioning
confidence: 99%
“…Second, some studies suggested that the familiar size of objects can be automatically retrieved from memory. For instance, Ferrier, Staudt, Reilhac, Jiménez and Brouillet (2007) reported that objects associated with a large or small familiar size prime categorical judgments of objects with a close familiar size compared to objects with an important size difference. It is noteworthy that in this experiment, objects were presented with a constant visual size supporting the critical involvement of the familiar size rather than the visual one (see also Long, Konkle, Cohen & Alvarez, 2016;Long & Konkle, 2017 for converging evidences).…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, it seems that the known size of objects can be automatically retrieved even when objects are briefly perceived suggesting the possible automatic retrieval of ARPF during fast real interactions with objects. Ferrier et al ( 2007 ) have for example demonstrated that a target picture (e.g., an elephant) is easily categorized as an animal when the brief prime picture (150 ms) has a similar known size (e.g., a giraffe or a car) rather than a different (e.g., a bee or a key) while both pictures have the same visual size on the screen (see also Setti et al, 2009 ; Gabay et al, 2013 ). It is noteworthy that the size is generally stable across items of a category as well as across experiences.…”
mentioning
confidence: 99%